2018
DOI: 10.1021/acs.analchem.7b04281
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Glycosylation Assay for Urinary Prostate-Specific Antigen

Abstract: The concentration of prostate-specific antigen (PSA) in serum is used as an early detection method of prostate cancer (PCa); however, it shows low sensitivity, specificity, and a poor predictive value. Initial studies suggested the glycosylation of PSA to be a promising marker for a more specific yet noninvasive PCa diagnosis. Recent studies on the molecular features of PSA glycosylation (such as antenna modification and core fucosylation) were not successful in demonstrating its potential for an improved PCa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 29 publications
0
44
0
1
Order By: Relevance
“…Furthermore, isomeric α2,3- and α2,6-sialoglycopeptides possess different electrophoretic mobilities facilitating their separation using capillary electrophoresis (CE)-ESI-MS [ 185 , 186 ]. Recent improvements in the CE hyphenation methods have increased the sensitivity and reproducibility of glycopeptide analysis by CE-MS [ 187 , 188 ] and opened interesting avenues for CE-based glycoproteomics [ 189 ].…”
Section: Innovations In Structure-focused Glycoproteomicsmentioning
confidence: 99%
“…Furthermore, isomeric α2,3- and α2,6-sialoglycopeptides possess different electrophoretic mobilities facilitating their separation using capillary electrophoresis (CE)-ESI-MS [ 185 , 186 ]. Recent improvements in the CE hyphenation methods have increased the sensitivity and reproducibility of glycopeptide analysis by CE-MS [ 187 , 188 ] and opened interesting avenues for CE-based glycoproteomics [ 189 ].…”
Section: Innovations In Structure-focused Glycoproteomicsmentioning
confidence: 99%
“…. Later, a glycosylation assay for PSA analysis in urine was developed by the same group, based on a similar CE method in combination with dopant (ACN) enriched nitrogen gas to enhance sensitivity . In addition, the Dovichi group observed an improved resolution of different N ‐glycopeptide species with the same peptide sequence, especially if differentially sialylated, compared to RPLC .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Aiming for an improved PSA test, glycosylation of PSA has recently been described based on glycopeptide analysis, in which a total of 67 N-glycopeptides (proteoforms!) were identified [56]. Here it was concluded that PSA proteoform profiling might be a promising tool for the determination of potential glycomic biomarkers for the differentiation between aggressive PCa, indolent PCa and benign prostate hyperplasia in larger cohort studies.…”
Section: Figurementioning
confidence: 86%